Влияние биологических и социальных факторов на развитие мыслительной и речевой способности у детей - Часовская, М.А. (Культура народов Причерноморья, 2003)
Biological and social evolution of the human person has caused occurrence of a universal remedy of the communication – language. Language is the most comprehensive and most differentiated means of expression, which the person owns. Besides language is a very complex sign system which requires constant research. There is no doubt, that the research of children's speech can discover numerous laws in development of phonetic, lexical and syntactic structures.